The Self-nanoemulsifying Drug Delivery System Formulation of Mefenamic Acid - Suryani, Suryani (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Mefenamic acid is one of the nonsteroidal anti-inflammatory drugs that have analgesic, antipyretic, and anti-inflammatory properties. However, in the biopharmaceutical classification system, mefenamic acid is included in Class II compounds with low oral bioavailability based on its dissolution rate or solubility in the digestive tract. One way to overcome the solubility problem of mefenamic acid is by formulating it into self-nanoemulsifying drug delivery system (SNEDDS). Previous research has shown that self-emulsifying drug delivery system of mefenamic acid produced greater drug solubility. In our research, we formulated SNEDDS of mefenamic acid to improve its solubility. SNEDDS is a mixture of isotropic oil, surfactants, cosurfactants, and drugs that form nanoemulsion oil in water when emulsified in water. The aim of this study was to formulate mefenamic acid SNEDDS using two different oil phases and compare their characteristics. Materials and Methods: Mefenamic acid SNEDDS formulation was carried out using the oil phase (olive oil and virgin coconut oil [VCO]), surfactant (tween 80 and tween 20), and cosurfactant (propylene glycol and polyethylene glycol [PEG] 400) with various concentrations. Optimization of the mefenamic acid SNEDDS formula was determined by observing the emulsification and clarity times, which were clarified with % transmittance. Then, further characterization of particle size, potential zeta, and stability was conducted. Results and Discussion: The optimization results obtained by F24 had a composition of olive oil, tween 80, and PEG 400 with a ratio of 1:8:1 and the results obtained by F53 had a composition of VCO, tween 80, and PEG 400 with a ratio of 1:5:1 meeting the requirements with emulsification time of 57 and 50 s, and transmittance values of 90% and 95%. The characterization results showed that F24 with the composition of olive oil, tween 80, and PEG 400 ratio 1:8:1 had a particle distribution of 569.4 nm, zeta potential +9.0 mV, and stability in gastric fluid media. Meanwhile, the characterization results showed that F53 having the composition of VCO, tween 80, and PEG 400 with the ratio of 1:5:1 had a particle distribution of 16.8 nm, zeta potential +2.9 mV, and stability in gastric fluid media. Conclusion: Based on the data, it can be concluded that the oil phase of VCO produced mefenamic acid SNEDDS formulas, which are better than the olive oil phase.